Pengaruh Literasi Keuangan, Kepercayaan dan Keamanan Terhadap Transaksi Pengguna QRIS pada Generasi Z di Desa Sukamulih Tasikmalaya - Miranda Maryam; Heidi Siddiqa (MAMEN: Jurnal Manajemen, 2026)
The advancement of digital technology has shifted the payment system toward cashless transactions, one of which is through the Quick Response Code Indonesian Standard (QRIS), with Generation Z representing the most potential user group. This study aims to determine the effect of digital financial literacy, trust, and security on QRIS usage among Generation Z in Sukamulih Village, Tasikmalaya. Using primary data gathered from questionnaires and observations, the research data was processed through multiple linear regression analysis using the SPSS application.The t-test results indicate that digital financial literacy has a positive and significant effect on QRIS usage (t = 6.056; sig. = 0.000). The security variable also shows a positive and significant influence (t = 6.717; sig. = 0.000). However, the trust variable surprisingly shows a negative and significant effect on the utilization of QRIS (t = -5.004 sig. = 0.000 ). Through the F-test, it is proven that digital financial literacy, trust, and security simultaneously have a significant effect on QRIS usage ( F = 48.201;sig. < 0.001). The coefficient of determination (R2) value of 0.515 indicates that 51.5% of the variation in QRIS usage is influenced by these three variables, while the remaining 48.5% is explained by other factors outside this study. These findings emphasize the importance of strengthening digital financial literacy and ensuring payment system security to optimize QRIS adoption among Generation Z.